2018
DOI: 10.1038/s41598-018-35084-1
|View full text |Cite
|
Sign up to set email alerts
|

The shift in ocular dominance from short-term monocular deprivation exhibits no dependence on duration of deprivation

Abstract: Deprivation of visual information from one eye for a 120-minute period in normal adults results in a temporary strengthening of the patched eye’s contribution to binocular vision. This plasticity for ocular dominance in adults has been demonstrated by binocular rivalry as well as binocular fusion tasks. Here, we investigate how its dynamics depend on the duration of the monocular deprivation. Using a binocular combination task, we measure the magnitude and recovery of ocular dominance change after durations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 32 publications
2
60
1
Order By: Relevance
“…27,58 This intriguing phenomenon is observed when SED was measured with either the BR or binocular phase combination methods. To reveal the characteristics of short-term deprivation, Min et al 33,34 investigated if the boost in SED could be increased (cumulative effect) with longer deprivation duration or repeated deprivations over several days. Interestingly, they found no cumulative effect, which suggested to them that the phenomenon acts in an all-or-none fashion.…”
Section: Short-term Monocular Deprivation Temporarily Boosts Sensory mentioning
confidence: 99%
“…27,58 This intriguing phenomenon is observed when SED was measured with either the BR or binocular phase combination methods. To reveal the characteristics of short-term deprivation, Min et al 33,34 investigated if the boost in SED could be increased (cumulative effect) with longer deprivation duration or repeated deprivations over several days. Interestingly, they found no cumulative effect, which suggested to them that the phenomenon acts in an all-or-none fashion.…”
Section: Short-term Monocular Deprivation Temporarily Boosts Sensory mentioning
confidence: 99%
“…We have suggested that a GABA-mediated account could have contributed to the surround facilitative effects in Experiment 3. Given this, increasing the duration of deprivation would enhance surround facilitative effects in the immediate post-deprivation period, but in a gradual manner akin to the small DE increase observed in Min et al (i.e., 25% increase in magnitude over a 20-fold increase in deprivation duration) 19 . It is unclear at this point if the maintenance of these surround facilitative effects depends on GABAergic concentration or are supported by longer-term mechanisms that are activated with longer deprivation durations.…”
Section: Discussionmentioning
confidence: 90%
“…While most studies interested in the effects of short-term monocular deprivation have typically employed hours of monocular deprivation, e.g., 2.5 h 10 , 12 17 , two recent studies have shown that the DE can be obtained with shorter deprivation durations. For example, Min et al discovered that the interocular contrast balance ratio on a binocular combination task varies little with deprivation durations, producing only a 25% increase in the DE for a 300-min deprivation period compared to a 15-min deprivation period 19 . Similarly, Kim et al found that 15 min of CFS exposure was capable of producing significant shifts in BR dominance that temporarily strengthened the deprived eye 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new form of neural plasticity has been reported in adults. Patching one eye (i.e., monocular patching) for a short period (0.5-5 h) of time increases the contribution of the patched eye in binocular vision (Lunghi et al, 2011;Zhou et al, 2013a,b;Bai et al, 2017;Kim et al, 2017;Min et al, 2018Min et al, , 2019Ramamurthy and Blaser, 2018). The change, which is referred to as short-term ocular dominance plasticity (Lunghi et al, 2015a), is linked to the primary visual cortex (Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%